MiR‐540 as a Novel Adipogenic Inhibitor Impairs Adipogenesis Via Suppression of PPARγ. Issue 6 (10th April 2015) - Chen, Lin; Chen, Yuanwei; Zhang, Sheng; Ye, Lanfeng; Cui, Junhui; Sun, Quan; Li, Kaide; Wu, Hanjiang; Liu, Lei
ABSTRACT: A better understanding of the molecular mechanisms in adipogenesis may provide new insights into adipose tissue‐related diseases. Recently, microRNAs (miRNAs) have emerged as a class of epigenetic regulators of stem cell differentiation. In this study, we found that miR‐540 was an essential negative regulator of adipogenic differentiation in adipose tissue‐derived stromal cells (ADSCs). Lentivirus‐mediated overexpression of miR‐540 resulted in blockade of the expression of C/EBP‐α and PPARγ, the two master transcription factors of adipogenesis, and deficient lipid accumulation, whereas inhibition of miR‐540 promoted these processes. Target gene reporter assays showed that miR‐540 directly targeted the 3′‐untranslated region (3′UTR) of PPARγ, resulting in a decrease of PPARγ protein expression. Collectively, these data suggest that miR‐540 represents a new adipogenic inhibitor by, at least in part, targeting PPARγ. J. Cell. Biochem. 116: 969–976, 2015. © 2015 Wiley Periodicals, Inc.